Jackson-type inequalities with generalized modulus of continuity and exact values of the $n$-widths of the classes of $(ψ,β)$-differentiable functions in $L_2$. II - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
In the space $L_2$, we determine the exact values of some $n$-widths for the classes of functions such that the generalizedmoduli of continuity of their $(ψ, β)$ - derivatives or their averages with weight do not exceed the values of the majorants $Φ$ satisfying certain conditions. Specific examples of realization of the obtained results are also analyzed.